2022
DOI: 10.1038/s41597-022-01225-5
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing of adult rat testes after Leydig cell elimination and restoration

Abstract: Spermatogenesis is an efficient, complex, and highly organized proliferation and differentiation process that relies on multiple factors including testosterone produced by the Leydig cells. Although the critical role played by testosterone in spermatogenesis is well recognized, the mechanism by which it works is still not completely understood, partially due to the inability to specifically and precisely monitor testosterone-dependent changes within developing germ cells. Here we present single-cell RNA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Next, we integrated published single cell RNA-seq ( scRNA-seq ) datasets of adult rat testicular cells (28) with our bulk RNA-seq datasets from PND 60 Taf7l Xm+/Y and Taf7l Xm-/Y testes to identify specific transcript-associations with each spermatogenic cell type. The dataset integration indicated that TAF7L deficiency led to an enrichment of spermatogonia genes, and a downregulation of genes associated to spermatocytes and spermatids ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we integrated published single cell RNA-seq ( scRNA-seq ) datasets of adult rat testicular cells (28) with our bulk RNA-seq datasets from PND 60 Taf7l Xm+/Y and Taf7l Xm-/Y testes to identify specific transcript-associations with each spermatogenic cell type. The dataset integration indicated that TAF7L deficiency led to an enrichment of spermatogonia genes, and a downregulation of genes associated to spermatocytes and spermatids ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we integrated published single‐cell RNA‐seq (scRNA‐seq) datasets of adult rat testicular cells 33 with our bulk RNA‐seq datasets from PND 60 Taf7l +/ Y and Taf7l −/ Y testes to identify specific transcript‐associations with each spermatogenic cell type. The dataset integration indicated that TAF7L deficiency led to an enrichment of spermatogonia genes and a downregulation of genes associated with spermatocytes and spermatids (Figure 4C,D).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, many traditional methods such as Principal Component Analysis (PCA), Non-Negative Matrix Factorization (NNMF), and Latent Dirichlet Distribution (LDA) come with limitations tied to their linearity. Nonlinear dimensionality reduction methods such as t-distributed stochastic neighbor embedding (t-SNE) have gained popularity in recent years for omics data analysis [ 39 42 ]. Nevertheless, these methods fall short in projecting new data into an already computed embedding.…”
Section: Introductionmentioning
confidence: 99%